2015
DOI: 10.1680/gein.15.00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperatures on the physical and mechanical properties of HDPE geomembranes in air

Abstract: The effect of elevated temperatures, particularly between 95 and 115°C as encountered in some geoenvironmental applications, on the physical and mechanical properties of high-density polyethylene (HDPE) geomembranes (GMBs) is examined. Four commercially available HDPE GMBs were incubated in air at temperatures ≥ 85°C. Investigation of the thermograms by differential scanning calorimetry showed a significant change in the polymer morphology with an increase of the incubation temperature and duration, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…It is worth noting that L c before annealing was evaluated at 171 Å, which is consistent with results previously found by Tireau on an HDPE matrix. The appearance of a second melting peak is driven by the recrystallization of secondary thinner melted crystals during the cooling step after annealing . Moreover, the rapid increase in X c and %P accompanied with a sharp decrease in %S and T ms for short annealing times suggests that a significant amount of recrystallization by an “annealing effect” occurred as previously evidenced by some authors .…”
Section: Effect Of An Annealing Process At 125°csupporting
confidence: 65%
See 2 more Smart Citations
“…It is worth noting that L c before annealing was evaluated at 171 Å, which is consistent with results previously found by Tireau on an HDPE matrix. The appearance of a second melting peak is driven by the recrystallization of secondary thinner melted crystals during the cooling step after annealing . Moreover, the rapid increase in X c and %P accompanied with a sharp decrease in %S and T ms for short annealing times suggests that a significant amount of recrystallization by an “annealing effect” occurred as previously evidenced by some authors .…”
Section: Effect Of An Annealing Process At 125°csupporting
confidence: 65%
“…Post‐annealing was performed at T a = 125°C thus at a temperature that was located in the first part of the HDPE melting peak (see Fig. ) and allowed possible restructuration of the crystalline phase as demonstrated by some authors . It is important to keep in mind that this process was performed under air conditions that could involve potential chemical modification and degradation phenomena.…”
Section: Effect Of An Annealing Process At 125°cmentioning
confidence: 99%
See 1 more Smart Citation
“…In HDPE geomembranes, temperatures in the range of 80 °C to 90 °C are suggested as the maximum. Temperatures around 105 °C or higher should be avoided because the melting point of polyethylene is 125 ºC (KOERNER, 2005;ISLAM et al, 2011;KOERNER et al, 2007;ABDELAAL et al, 2015).…”
Section: Thermal Degradationmentioning
confidence: 99%
“…The results of these immersions showed that thermogravimetric analysis did not show changes in thermal stabilities, but an average decrease was noted in the tensile yield strength of 34 % for the vinasse sample and an expressive tear strength loss of 40 % was verified in the sodium hydroxide sample. Four different high-density polyethylene geomembranes, 1.5 mm thick, incubated in air at high temperatures were evaluated by Abdelaal et al (2015). These aging samples were investigated by oxidative-induction time tests (standard and high-pressure), the melt flow index test, the stress cracking test (single point), and the morphological changes due to annealing, using the differential scanning calorimetry (DSC).…”
Section: Laboratory Studies Of Hdpe Geomembrane Durabilitymentioning
confidence: 99%